2020
DOI: 10.1101/2020.08.18.256321
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Large-scale Comparison of Cortical and Subcortical Structural Segmentation Methods in Alzheimer’s Disease: a Statistical Approach

Abstract: Alzheimer's disease (AD) is a neurodegenerative disease that leads to anatomical atrophy, as evidenced by magnetic resonance imaging (MRI). Automated segmentation methods are developed to help with the segmentation of different brain areas. However, their reliability has yet to be fully investigated. To have a more comprehensive understanding of the distribution of changes in AD, as well as investigating the reliability of different segmentation methods, in this study we compared volumes of cortical and subcor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 154 publications
(158 reference statements)
0
5
0
Order By: Relevance
“…Our method was based on volumetric data: brain images were segmented into smaller brain areas over the cortex (volBrain and CAT) as well as hippocampus (HIPS) using standardised brain atlases. Therefore, the individual components involved in the optimisation algorithms reflect the size of each brain area, which is extremely interpretable 26 . This is in contrast to optimisation methods based on deep neural networks and support vector machines that are mostly considered as black boxes 42 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our method was based on volumetric data: brain images were segmented into smaller brain areas over the cortex (volBrain and CAT) as well as hippocampus (HIPS) using standardised brain atlases. Therefore, the individual components involved in the optimisation algorithms reflect the size of each brain area, which is extremely interpretable 26 . This is in contrast to optimisation methods based on deep neural networks and support vector machines that are mostly considered as black boxes 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, there is no need for particular expertise to use these tools, which makes them more accessible and more practical in clinical settings. The validity of these methods, however, is still to be fully studied 17 , 26 , 60 62 . In particular, their level of accuracy in segmentation of brains with different disorders (such as those with atrophy) is less clear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, in two studies, we showed that T1-weighted MRI (structural MRI; sMRI) can be used in classification of AD and MCI. Indeed, the majority of early studies looking at classification of AD and HC was done on sMRI [ 22 ]. This is mostly due to costs and accessibility of sMRI data [ 23 ].…”
Section: Introductionmentioning
confidence: 99%